Predicting Factors Affecting the Behavior of Healthcare Employees in the Use of Personal Protective Equipment During Epidemics Based on Godin et al’s Model: A Study in Iran - Milad Ahmadi Marzaleh; Peivand Bastani; Abolfazl Raeyat Mohtashami; Payam Farhadi; Saeed Ghanbari; Ramin Ravangard (Health Services Insights)
Background: Protecting healthcare employees and preventing infection transmission are paramount concerns during epidemics. Predicting healthcare employees’ behavior regarding the use of personal protective equipment (PPE) and identifying the related effective factors can guide educational and administrative strategies and enable timely interventions during outbreaks. This study aimed to predict factors affecting the healthcare employees’ behavior in the use of PPE at Shiraz University of Medical Sciences in Iran, based on Godin et al’s model. Methods: This was a cross-sectional and descriptive-analytical study. After reviewing the related articles and interviewing the experts and based on the model of Godin et al. (2008), a questionnaire was developed, validated, and tested for reliability using face and content validity as well as Cronbach’s alpha. Collected data were analyzed using SPSS v.21 and modeled by Structural Equation Modeling (SEM) via SPSS v.21 and Smart PLS v.3 software. Results: The questionnaire was valid (CVI = 86.42, CVR = 81.71) and reliable (α = .85). The model exhibited appropriate measurement, structural, and overall fit. Beliefs about consequences, social influences, habits/past behavior, role and identity, characteristics of employees, moral norms, and beliefs about capabilities indirectly and significantly influenced behavior ( P  < .001). Additionally, beliefs about capabilities ( P  < .001), habits/past behavior ( P  = .001), and intention ( P  = .001) directly and significantly influenced PPE use behavior during epidemics. Conclusion: The results emphasized the necessity of targeted interventions based on the studied model constructs within healthcare organizations. By promoting positive beliefs about PPE effectiveness and encouraging appropriate intentions and behaviors, healthcare organizations can significantly improve employee’s adherence to PPE use during pandemics.